The Effect of NaOH Concentration on Cellulose Levels of Kepok Banana Hump (Musa paradisiaca L.) - Surya Ningsi; Nurshalati Tahar; Nur Azizah Syahrana; Yuri Erika Arifin (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2020)
The high cellulose content of Kepok banana hump has great potential to be used as a pharmaceutical excipient. This research aims to determine the effect of NaOH concentration on cellulose levels from kepok banana hump. NaOH solution was made in five concentrations, namely 5%; 7.5%; 10%; 12.5% and 15%. Cellulose levels were analyzed using the Chesson method. The research results showed that the NaOH solution with a concentration of 5%; 7.5%; 10%; 12.5% and 15% yielded cellulose content of 12.5%, 15.9%, 64.9%, 60.7% and 41.9%. The highest cellulose content is produced at a concentration of 10% NaOH solution.